2018
DOI: 10.1371/journal.pone.0203084
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic steatohepatitis-like pattern in liver biopsy of rheumatoid arthritis patients with persistent transaminitis during low-dose methotrexate treatment

Abstract: ObjectiveThe mechanism of liver injury with low-dose methotrexate (MTX) is incompletely understood. This study was designed to evaluate the association between non-alcoholic fatty liver disease (NAFLD) and liver injury during MTX treatment for rheumatoid arthritis (RA).MethodsBetween October 2014 and May 2015, we enrolled all MTX users for RA and monitored participant serum hepatic transaminase levels for 1 year. All patients had normal transaminase levels before the first MTX prescription. Using diagnostic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 59 publications
2
40
1
1
Order By: Relevance
“…5 Shunshuke Mori et al in their observational study of 846 RA found that 42 patients using methotrexate had persistent elevation of transaminases while ultrasound showed fatty liver disease and histological results revealed nonalcoholic steatoheapatitis as most prevalent pattern of liver injury, there was no significant impact of methotreaxte dose and duration on histological severity. 6 Systematic review by Salliot and van der Heijde identified increased levels of transaminases (ALT, AST) as the second most frequent adverse effects with methotrexate therapy (20.2%) after gastrointestinal probelms. 7 I t is found that fatty liver disease (NAFLD), diagnosed either by imaging or biopsy, has been associated with methotrexate therapy since long.…”
Section: Introductionmentioning
confidence: 99%
“…5 Shunshuke Mori et al in their observational study of 846 RA found that 42 patients using methotrexate had persistent elevation of transaminases while ultrasound showed fatty liver disease and histological results revealed nonalcoholic steatoheapatitis as most prevalent pattern of liver injury, there was no significant impact of methotreaxte dose and duration on histological severity. 6 Systematic review by Salliot and van der Heijde identified increased levels of transaminases (ALT, AST) as the second most frequent adverse effects with methotrexate therapy (20.2%) after gastrointestinal probelms. 7 I t is found that fatty liver disease (NAFLD), diagnosed either by imaging or biopsy, has been associated with methotrexate therapy since long.…”
Section: Introductionmentioning
confidence: 99%
“…Studies which show improvements in liver function tests when MTX is discontinued or interrupted, raise the possibility of MTX being an accelerating risk factor 69 . Interestingly, Mori et al found that a NASH‐like pattern was the most prevalent in biopsies of MTX‐treated RA patients with persistent transaminitis and abnormal ultrasound findings 10 . We therefore speculate whether MTX has the potential to ‘destabilise’ NAFLD into the more concerning subtype, NASH, in certain individuals.…”
Section: Discussionmentioning
confidence: 78%
“…10,68 Similarly, the histological findings of both conditions are quite indistinguishable and in studies with pre-MTX treatment liver biopsies, fibrotic change has been reported in 14% of patients. 10,24 Studies which show improvements in liver function tests when MTX is discontinued or interrupted, raise the possibility of MTX being an accelerating risk factor. 69 Interestingly, Mori et al found that a NASH-like pattern was the most prevalent in biopsies of MTX-treated RA patients with persistent transaminitis and abnormal ultrasound findings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For RA patients, several studies identified obesity, type 2 diabetes and hypercholesterolaemia as risk factors for the increase in alanine and/or aspartate aminotransferase (ALT and/or AST) levels that is observed during MTX treatment [ 16–19 ]. A NASH-like pattern was reported to be a common histological abnormality in MTX-treated RA patients who had persistent transaminitis [ 19 ]. These findings suggest that use of MTX could favour aggravation of pre-existing NAFLD and progression to NASH.…”
Section: Introductionmentioning
confidence: 99%